Eyespot configuration and predator approach direction affect the antipredator efficacy of eyespots - Skelhorn, John; Rowland, Hannah M. (Frontiers in Ecology and Evolution, 2022)
Many prey species possess eyespots: paired markings that often consist of two or more concentric circles. Predators are wary of such prey because eyespots are conspicuous and/or mistaken for vertebrate eyes. Here we used naïve domestic chicks as predators of artificial moth-like prey to test the hypothesis that both eyespots configuration and predator approach direction affect the antipredator efficacy of eyespots. We found that when chicks were allowed to approach prey straight on, eyespots configuration did not influence attack latency. Chicks that were permitted to approach from either the left or the right, however, were slower to attack prey in which the central circle of the eyespot was centrally placed or shifted in the direction of the chick’s approach, compared to prey in which the central circle had been shifted away from the direction of approach. These findings suggest that eyespots composed of concentric circles may protect prey from predators approaching from a wider range of directions than eyespots composed of eccentric circles. They are also consistent with the idea that eyespots are mistaken for eyes, and are perceived to pose a lesser risk when their “gaze” is averted from the approaching predator.